Efektivitas Pengembangan E-Modul Interaktif Bahasa Indonesia Materi Teks Prosedur Berbasis Canva - Maulinda, Tiara Nurul; Megawati, Erna; Rafidah, Firda (SAP (Susunan Artikel Pendidikan), 2024)
The need of interactive media in Indonesian language learning has become an urgent need to be fulfilled in the research location. The research aims consist of: 1) developing an interactive learning e-module product based Canva to produce a valid (worthy) learning media and 2) understanding effectiveness an interactive learning e-module product based Canva towards the writing skills of procedure text for SMA Fajrul Islam students. The method used was research and development a Borg and Gall model, with design quasi experimental post test only control group design. Data analyzed using descriptive statistical test through expert judgments validation for e-module, normality test, homogeneity test, and T test for e-module effectiveness. Research shows that interactive learning e-module product based Canva is very worthy of being used as a learning media with 100% material worth, 93% language worth, 81.3% media worth, teacher response is 100%, and students response is 96%. The e-module is also very effective against the writing skills of procedure text for SMA Fajrul Islam students with significant results from post test control class and experiment class with tcount = 13,1995 > ttable = 2,0189. Based on the data it can be concluded that the use of interactive learning e-module product based Canva is more effective than not with the use of interactive e-module for students of class XI SMA Fajrul Islam.